Dynamic spreading gain control in multiservice CDMA networks. - Seong-Jun Oh (IEEE Journal on selected areas in communications)
In this paper, we consider a direct-sequence code division multiple access (DS-CDMA) network consisting of a single radio access point and a collection of wireless terminals. The network offers two classes of service: class-1 (real-time) and class-2 (reliable). We are interested in studying the effect of dynamic spreading gain control (SGC) on the dynamics of multiple access interference (MAI), spectral efficiency, and the quality of service (QoS) experienced by each service class. We first consider a time-slotted system in which class-2 terminals operate in a random access fashion. We show that under optimal (throughput maximizing) dynamic SGC: (1) the optimal retransmission probability is equal to one, and (2) the optimal spreading gain increases linearly, or equivalently, the transmission rate decreases inverse linearly, as the MAI level increases. We then model the system as a continuous-time finite-source queueing system with processor sharing, and obtain an explicit (closed-form) expression for the stationary distribution of the number of active class-1 and class-2 terminals, that is, the MAI level. This distribution is used to derive expressions for various QoS measures and define a capacity or admissible region. The results obtained by simulation and analysis are in extremely close agreement. This work contributes to a better understanding of the relationships between QoS, multiple access interference, and allocation of radio resources in DS-CDMA networks